Teaching Dictation as a Way to Develop University Students' Writing Skills - Ibadillah, Banna Irfan; Syafi'i, Taqyuddin Ibnu; Bahruddin, Uril (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Dictation is the subject most neglected by teachers in teaching the Arabic Language, and they believe that it has no importance in developing students’ linguistic skills. Rather, they considered it an additional material with no value. This research aims to describe the method used in teaching dictation at STIBA Ar Raayah, Class of Linguistic Preparation, and to know the factors that help in its success, and the effects on developing students’ writing skills. The approach used in this research is the qualitative approach as a descriptive study. Data is collected through personal interviews, field observations, and documents. The results of the research are: (1) that the method used in teaching the subject of dictation at STIBA Ar Raayah is the method that contains the introduction, presentation, evaluation, and conclusion, and (2) that there are factors for the success of teaching the subject of dictation, and they are divided into internal, where student interaction and frequent training, and external, where memorizing vocabulary and training them in writing texts and using teaching aids, and (3) that dictation has a role in developing writing skills, as students are able to distinguish between correct and incorrect writing and improve writing.